2016
DOI: 10.1371/journal.pone.0161257
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pneumococcal Conjugate Vaccines (PCV7 and PCV13) against Invasive Pneumococcal Disease among Children under Two Years of Age in Germany

Abstract: BackgroundIn this study we calculate the effectiveness of pneumococcal conjugate vaccines (PCV) against invasive pneumococcal disease (IPD) among children under the age of two years using the indirect cohort method. We also discuss the timeliness of vaccination and the residual cases of vaccine type IPD.Methods and FindingsFrom July 2006 until June 2015, 921 IPD cases were reported and for 618 children (67.1%), the vaccination status at the time of infection could be accurately determined. Of these, 379 (61.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 21 publications
3
54
0
3
Order By: Relevance
“…It has been hypothesized that this may be due to the different conjugation methods used for 19F in the two vaccines [92]. PHiD-CV has no impact on serotype 3 disease while effectiveness of PCV13 against serotype 3 disease has been observed in some but not other studies [93][94][95][96]. Serotype-specific information was available for eight children and five adult datasets.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that this may be due to the different conjugation methods used for 19F in the two vaccines [92]. PHiD-CV has no impact on serotype 3 disease while effectiveness of PCV13 against serotype 3 disease has been observed in some but not other studies [93][94][95][96]. Serotype-specific information was available for eight children and five adult datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination in newly arrived refugees presents an opportunity to cost-effectively, safely, and humanely protect a vulnerable population from negative health outcomes resulting from vaccine-preventable diseases ( 13 ). Given that children in Germany with insecure residence status are twice as likely to be incompletely vaccinated ( 2 ), a PCV program for refugee children in Germany might require additional follow-up measures to ensure consistency and provide sufficient protection, particularly because PCV dosing in Germany-born children with IPD has been lax ( 9 ). A PCV program could help reduce antimicrobial drug–resistant pneumococcal infections, the carriage of resistant strains ( 14 ), overall antimicrobial drug use, and the prevalence of resistance genes within the pneumococcal population ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the analysis, case isolates were from refugee children with IPD, and control isolates were from Germany-born children with IPD. Refugee status was documented by GNRCS personnel in conjunction with determining vaccination status, as described elsewhere ( 9 ). Because identification of refugee status was tied to the determination of vaccination status, all children with an unknown vaccination status were excluded.…”
Section: The Studymentioning
confidence: 99%
“…The study showed a VE of 83% (95% CI 41; 95) against 19A IPD and VE of 100% against IPD due to serotype 7F. An indirect cohort analysis carried out in Germany [6] in children aged 2-24 months, who received at least one dose of PCV13 from July 2010 till June 2015, showed a VE of 77% (95% CI 47; 90) and 84% (95% CI 18; 98) against IPD due to 19A and 7F, respectively. Likewise, an indirect cohort analysis conducted in children aged 4-56 months in the UK [7] showed a VE of 67% (95% CI 33; 84) against 19A IPD and 91% (95% CI 70; 98) against 7F IPD following PCV13 introduction.…”
Section: Letter To the Editormentioning
confidence: 90%